Application of Fuzzy Logic in Tempe Production Using the Tsukamoto Algorithm - Aliya Fidella; Daffa Zulqisthi; Muhammad Faiz Assariy; Mrr Lukie Trianawati; Syafira Aristawidya; Chandradewi Ekaputri; Hafizhah Nur Humairah; Gita Aisy Affatunnisa; Muhammad Ghifari Fazan Putra; Chika Hayya Sabillah (Batrisya Education, 2025)
Fuzzy logic is widely used in various fields to formalize human behavior by considering inaccurate or partial reasoning. This study implements the Tsukamoto fuzzy logic method to analyze tempe production based on demand and inventory data. The research utilizes library research methods and data analysis using MATLAB (Matrix Laboratory). The Tsukamoto method was chosen for its high tolerance for data and flexibility. The system uses two input variables: demand and inventory, with output being production quantity. The fuzzy sets for demand are categorized as